Technology-Enhanced Learning in Audiovisual Education: The Case of Radio Journalism Course Design - Maria Matsiola; Panagiotis Spiliopoulos; Rigas Kotsakis; Constantinos Nicolaou; Anna Podara (MDPI AG, 2019)
Journalism is in a state of perpetual change due to the implementation of technological tools on an everyday basis. In the contemporary news distribution environment, the boundaries between media are no longer distinct, therefore media/journalism educational institutions should adapt curricula according to the needs of each type of medium. The aim of this paper is to present the incorporated technologies in the radio journalism undergraduate course of the School of Journalism and Mass Communications at the Aristotle University of Thessaloniki and evaluate their necessity according to the students themselves. After the completion of the course, which involves the use of specialized technological tools in audio recording and editing, a survey employing quantitative method based on the technology acceptance model was conducted. The results indicate that the students, despite the difficulties that were encountered due to the initial lack of knowledge on the technology applied, evaluated very highly both their satisfaction with the produced outcome and the usefulness of the procedure. In fact, the major result is that perceived usefulness is a key factor that determines the utilization of specialized technology.